2013
DOI: 10.1002/mrm.24582
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated fractional ventilation imaging with hyperpolarized Gas MRI

Abstract: PURPOSE To investigate the utility of accelerated imaging to enhance multi-breath fractional ventilation (r) measurement accuracy using HP gas MRI. Undersampling shortens the breath-hold time, thereby reducing the O2-induced signal decay and allows subjects to maintain a more physiologically relevant breathing pattern. Additionally it may improve r estimation accuracy by reducing RF destruction of HP gas. METHODS Image acceleration was achieved by using an 8-channel phased array coil. Undersampled image acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Also, involuntary exposure of non-smokers to tobacco smoke has a negative effect on the lungs, especially for exposed children [ 31 ]. Such changes would result in a more uneven ventilation distribution compared to healthy subjects who never smoked [ 13 ] and therefore an increased AUC(CV > 20%) value. In this small pilot study, we found a tendency of ex-smokers to have a higher AUC(CV > 20%) value than subjects who never smoked and current smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, involuntary exposure of non-smokers to tobacco smoke has a negative effect on the lungs, especially for exposed children [ 31 ]. Such changes would result in a more uneven ventilation distribution compared to healthy subjects who never smoked [ 13 ] and therefore an increased AUC(CV > 20%) value. In this small pilot study, we found a tendency of ex-smokers to have a higher AUC(CV > 20%) value than subjects who never smoked and current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Narrowing of the airways is caused by inflammation, secretions and the shortening of muscle fibres around the bronchial walls, which obstructs airflow. Emami et al [ 13 ] showed that asymptomatic smokers had a more heterogeneous ventilation distribution compared to healthy non-smokers. Patchiness can be caused by narrowing of both larger and smaller airways.…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of the technique has been particularly recognized for HP 3 He to diagnose pulmonary diseases in small rodents (8,9). Ongoing efforts are being made to improve the technique, and now it is applicable from small rodents to humans (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances combining SSFP imaging with cheaper natural abundance (∼26%) HP 129 Xe gas has recently shown promise for ventilation‐weighted imaging . Parallel imaging with HP gases has also been explored but widespread implementation has been slowed by hardware costs for multichannel RF‐coils and compatibility with multinuclear clinical MRI systems. This is a ripe area for future advances in FLI using both HP and fluorinated gases.…”
Section: Gas Properties and Imaging Strategiesmentioning
confidence: 99%